Analysis of Water Quality in The Srigangga River Flow, Central Lombok - Supardiono Supardiono; Rachmawati Noviana Rahayu; Isrowati Isrowati; Ernawati Ernawati (Jurnal Penelitian Pendidikan IPA, 2023)
The Srigangga River is one of the main rivers flowing into the Batujai Reservoir basin in Central Lombok Regency, West Nusa Tenggara Province. Communities around this area still use river water to fulfill their daily needs. The many activities of residents around this river area affect the decline in river water quality. This research aims to determine river water quality based on physical, chemical, and biological parameters and determine the river water pollution index using the pollution index method. This type of research is a descriptive research method with a laboratory-based approach; sampling locations are carried out in the river's upstream, middle, and downstream parts. The parameters analyzed include pH, TSS, DO, COD, BOD, Phosphorus content, total coliform, and Escherichia coli. The research results show that of the 8 (eight) parameters tested in the upstream, middle, and downstream parts of the Srigangga River, 4 (four) parameters are above the quality standards determined based on PP RI No.22 of 2021. The water pollution index value shows that the Srigangga River is already polluted in the light category